Can corporate social responsibility bias lending decisions?. Issue 4 (1st October 2016) - Guiral, Andres; Moon, Doocheol; Perez-Garcia, Javier
ABSTRACT: Recent research suggests that the effect of Corporate Social Responsibility performance (CSRp) on firm value is conditional on its ability to influence stakeholders through customer awareness. This study extends previous research using an experiment to investigate whether the impact of CSRp ratings on lending decisions is moderated by the level of customer awareness. Results using experienced loan officers from an international commercial bank indicate that lending decisions are likely to be biased since CSRp ratings are interpreted as a signal for superior financial performance regardless of the level of customer awareness. Our findings suggest that loan officers are susceptible to further training in the correct interpretation of CSRp.